The method of expert assessment of the technical condition of an automobile engine after overheating - Khrulev, A. E.; Saraiev, O. V.; Хрулєв, О. Е.; Сараєв, О. В. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. For expert studies of the technical condition of a car, a difficult task is to determine the causes and development of malfunction of engine mechanisms and systems. The paper proposes a model of engine malfunction during overheating, including in emergency mode caused by rapid loss of coolant. It has been established that thermal damage to the cylinder head is possible within 10 seconds after the cooling failure. The piston heats up more slowly and can only be damaged in the upper part and for a much longer time. According to the results of the study, it was found that in the event of an emergency loss of coolant, the driver does not have the technical ability to see the temperature rise, which may be important when investigating the causes of engine malfunctions associated with overheating. Goal. The goal is to investigate and reproduce the model of engine failure after overheating. Methodology. The theoretical calculated data are confirmed by real experimental studies of engine overheating failures. Results. It was calculated by calculation that in the absence of coolant, the temperature sensor, if it is located on the outlet pipe of the cylinder head, will not increase the temperature until the engine fails. A certain definite character of malfunction of parts of engine mechanisms during its sudden overheating is shown. Originality. On the basis of the developed models, a methodology was drawn up and the calculation of the thermal state of engine parts after overheating was performed. Practical value. The research carried out and the computational models compiled allow the expert to make a more objective assessment of the development of the engine malfunction mechanism when it overheats during the operation of the car.
Метод експертного оцінювання технічного стану автомобільного двигуна після його перегріву
Keywords: internal combustion engine; coolant; failure; overheating; двигун внутрішнього згоряння; теплоносій; несправність; перегрів; 621.432.3; 10.30977/AT.2219-8342.2021.48.0.5